Kapabilitas Pemasaran sebagai Mediasi Pengaruh Orientasi Pasar Orientasi Pembelajaran dan Orientasi Kewirausahaan terhadap Kinerja Pemasaran (Studi pada Usaha Menengah di Sulawesi Tenggara) - .., Halim; Hadiwidjojo, Djumilah; .., solimun; .., Djumahir (Jurnal Aplikasi Manajemen, 2012)
The purpose of this research is to develop market orientation and learning orientation and entrepreneurial orientation with reviewing the role of marketing in an effort to increase the capabilities of performance marketing. Research contributions are expected to be able to develop a marketing startegi which is a blend of marketing and strategic management. Sample research as much as 158 companies spread over 7 county/city in Southeast Sulawesi. Results of the analysis, with path analysis, found that the marketing capabilities serve as a full mediation which connects learning orientation and entrepreneurial orientation with the performance marketing. However the marketing capabilities haven't been able to market orientations mediated the relationship between on performance marketing. Market orientation of individually determine the performance marketing. Additional, The study found that the marketing capabilities influenced directly by the entrepreneurial orientation and learning orientation, but the orientation of the market instead of deciding the marketing capabilities.